Peran Guru Untuk Meningkatkan Keterampilan Motorik Halus Melalui Menggambar Pada Anak Bintang Timur Atambua: Indonesia - Olok, Wilhelmina; Lopo, Ferdinan; Bili, Lukas (Universitas Persatuan Guru 1945 NTT, 2023)
This study entitled Teachers' Role To Improve Smooth Motoric Skill Through Drawing In Children In Kindergarten Bintang Timur Atambua and conducted on the findings of problems related to fine motor in the Kindergarten Bintang Timur Atambua. The problem is some children who have not been able to creativity in drawing for it how the role of a teacher in giving a solution either in the form of approach, method or model of learning to handle it. The purpose of this study is to improve the fine motor skills of children through drawing techniques in children in Kaisarea Kindergarten Bintang Timur Atambua. Technique of collecting data in this research through observation, interview and documentation. Teknik analisis data used is a qualitative data analysis with the implementation of several stages such as data reduction, display data, and verification or withdrawal of conclusions. Recommendations given to early childhood educators are finger drawing lessons can be used as an alternative to improve the smooth motor creativity of children. There are several solutions as a teacher's role in improving children's fine motor through drawing techniques that the child is given the opportunity to draw with his own imagination by giving stimuli such as praise for his work and giving the opportunity to follow the competitions held through the school or cluster level after the child Get the award or the results achieved during the race should show the children who have not followed the race so as to motivate the children